1999
DOI: 10.1007/bf02743578
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for invasive thymoma and thymic carcinoma

Abstract: Postoperative radiotherapy with sufficient doses plays an important role as adjuvant treatment in complete or incomplete resected invasive Stage II to III thymoma. In unresectable thymoma Stage III to IV as well as in thymic carcinoma a multimodality approach should be considered to improve survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 28 publications
0
20
0
2
Order By: Relevance
“…As a result, most authors do not recommend the use of extended radiation fields routinely in cases of completely resected stage II disease. However, it is clear that total radiation dose is a significant prognostic factor in preventing local recurrence [31]. It has been suggested that patients with certain histological variants may have an increased risk of developing local recurrence in cases of completely resected thymoma.…”
Section: Radiotherapymentioning
confidence: 99%
“…As a result, most authors do not recommend the use of extended radiation fields routinely in cases of completely resected stage II disease. However, it is clear that total radiation dose is a significant prognostic factor in preventing local recurrence [31]. It has been suggested that patients with certain histological variants may have an increased risk of developing local recurrence in cases of completely resected thymoma.…”
Section: Radiotherapymentioning
confidence: 99%
“…Thymomas are generally considered cytological benign whereas thymic carcinomas have malignant cytological features. Thymic carcinomas have a significantly worse oncological prognosis (14)(15)(16).…”
Section: Thymomamentioning
confidence: 99%
“…Sıklıkla 1.8-2.0 Gy fraksiyon dozlarında uygulanan 50-60 Gy RT ile olgularda %90-100 olasılıkla lokal kontrol sağlanabilmektedir (23,24). Sınırda rezektable ya da unrezektable olgular neoadjuvan KT ya da torasik RT'den fayda görebilir (25). Kemoradyoterapinin rolü net değildir (26).…”
Section: Timik Karsinomunclassified